The Influence of Nonformal Education on Students' Cognitive Formation - Haris Pancawardana; Ibnu Imam Al Ayyubi; Rifqi Rohmatulloh; Murharyana Murharyana (Universitas Negeri Padang, 2023)
In the world of education, it is categorized into two, namely education in schools and education outside of school. Out-of-school education or it can be said that non-formal education is education for the community, in this case, students who need educational services to complement the deficiencies of formal education. This research was conducted at Tridaya Tutoring with a quantitative research approach. This research method uses survey methods and correlation analysis to see the interrelationships of students' creative thinking and critical thinking variables based on cognitive stages, namely formal, transitional, and concrete thinking stages. The population of this study were class XII students at Bimbel Tridaya with a sample of 53 students. The research instrument used tests and questionnaires. Obtained pretest data showed that there was a difference in the average initial ability of students in the experimental class and control class in creative and critical thinking and the average posttest final ability of creative and critical thinking of experimental class students was better than the average control class. The improvement of students' creative and critical thinking skills in the experimental class was obtained better than that of the control class students. Learning outcomes with students' cognitive levels at the formal, transitional, and concrete stages have differences and do not have a significant influence on the development of student learning outcomes, but there is an association between students' creative and critical thinking abilities.